Association of insomnia with suicide attempts in Chinese chronic schizophrenia patients with and without autistic symptoms - Wenzheng Li; Yu Liu; Rui Tao; Long Chen; Yang Liu; Daming Mo; Huanzhong Liu; Xiangyang Zhang (BMC Psychiatry)
Abstract Background Numerous studies have shown that people with schizophrenia (SCZ) have a higher risk of suicide, and insomnia symptoms are common in SCZ patients. Autism symptoms (AS) are common in SCZ patients, and they are strongly linked to suicide. This study explored the connection between insomnia, autistic symptoms, and suicide attempts in Chinese patients with SCZ, it has not yet been investigated. Methods 955 Chinese chronic SCZ patients provided demographic and clinical information for data collection. Insomnia Symptom Severity Index (ISI) was used to assess the severity of insomnia symptoms, and Beck Scale for Suicide Ideation (BSS) was used to assess the risk of suicide. PANSS Autism Severity Score (PAUSS) was used to assess autistic symptoms. Results The incidence of insomnia was higher in AS-SCZ patients than in non-AS-SCZ patients, but the incidence of suicide attempts was lower than that in non-AS-SCZ patients (all p < 0.05). In SCZ patients, insomnia severity scores were strongly associated with suicide attempts. Further correlational analysis showed that this association was only present in non-AS-SCZ patients (p < 0.05). Conclusions Insomnia in patients with chronic SCZ may be influenced by autistic symptoms, potentially impacting the association between suicide attempts and insomnia. Trial registration The study was a cross-sectional study, so there was no clinical trial registration. Clinical trial number: not applicable.